Penerapan Asas Menguntungkan Dalam Tindak Pidana Konservasi Sumber Daya Alam Hayati Dan Ekosistem (Studi Ketetapan Penghentian Penyidikan (SP-3) Nomor : S.Tap/27.B/X/Ditreskrimsus Polda Jambi tanggal 31 Oktober 2018) - Fajar Rudi Manurung; Syafruddin Kalo; Edi Yunara; mahmud mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2021)
Indonesia is a state based on law, all aspects of life within the territory of the Unitary State of the Republic of Indonesia must be based on the law and all laws in force in the territory of the Unitary State of the Republic of Indonesia. In the process of law enforcement for the protection of protected animals, a provision is needed to regulate it beforehand, rather than the act occurring in accordance with the provisions of Article 1 Paragraph (1) of the Criminal Code, to expect legal certainty for the perpetrators of criminal acts, in particular criminal acts of conservation of living natural resources ecosystem. If in the process of law enforcement, there is a change in a criminal act that regulates sanctions against the criminal act, then the most beneficial law enforcement must be carried out for the perpetrator. So that law enforcers in the process of investigating and prosecuting criminal acts of conservation of living natural resources and ecosystems are expected to have a balance between the preservation of protected animals and the laws and regulations that are still in force prohibiting these acts